F172. Comparison of inhalational anesthetic effects on cortical SEPs to upper limb and lower limb stimulation. (May 2018) - Legatt, Alan D.; Glover, Robert L.
Abstract : Introduction: During surgery on the thoracic and lumbar spine, SEPs to lower limb (LL) stimulation are used to monitor the dorsal column somatosensory pathways from the legs. SEPs to upper limb (UL) stimulation are often also recorded, to monitor for brachial plexus or peripheral nerve dysfunction related to the positioning of the patient's arms and to serve as a "control" for the effects of anesthesia on the LL SEPs. The latter use presumes that cortical SEPs to UL and LL stimulation are affected equally by anesthesia. We examined this assumption by measuring amplitude changes in UL and LL SEPs associated with the transition from TIVA (total intravenous anesthesia) with propofol and a narcotic to a halogenated inhalational anesthetic (HIA) during closing in a neurologically normal patient population. Methods: We retrospectively identified surgeries for idiopathic scoliosis in adolescents without neuromuscular disease during which there were no adverse SEP or MEP changes and at least 2 runs of both UL and LL SEPs were recorded after the transition to inhalational anesthesia. The average SEP amplitudes were calculated for those runs and for several SEP waveforms immediately preceding the anesthetic change. Percentage amplitude changes were calculated for SEPs for each limb, the results for the left and right sides were averaged together, and the amplitude ratios (amplitudes under HIA divided by amplitudes under TIVA) for UL SEPs were compared to those for LL SEPs. In all cases, the SEPs were elicited by ulnar nerve and posterior tibial nerve stimulation. Results: We identified 17 surgeries meeting inclusion criteria; desflurane was used in 9 and sevoflurane in 8. The patients included 12 girls and 5 boys ages 12–17 years. In one patient the UL SEPs were larger after the anesthetic change (amplitude ratio = 118%); in the other patients the amplitude ratio for UL SEPs ranged from 29% to 91%. Overall, the mean amplitude ratio for UL SEPs was 76%. For LL SEPs, the amplitude ratios ranged from 50% to 97% with a mean of 74%. In 10 patients the relative difference between the amplitude ratios for UL SEPs and LL SEPs was ⩽ 15% and in 6 patients it was between 16% and 40%. In the patient with the largest relative difference, the amplitude ratio was 29% for UL SEPs and 55% for LL SEPs. Conclusion: Cortical SEPs were almost always smaller under HIA than under TIVA. On average, the anesthetic effects in the UL SEPs were very similar to those in the LL SEPs (mean amplitude ratio 76% vs. 74%). The effects on UL SEPs versus LL SEPs were also similar in most individual patients, but there were some patients in whom the quantitative effects on UL SEPs and LL SEPs differed by more than 15%. In conclusion, in this patient population UL SEPs provide a good anesthetic control for LL SEPs overall, but it should not be assumed that they can accurately predict quantitative amplitude changes in LL SEPs in individual patients.